FREQUENCY OF HYPOCALCAEMIA AFTER SUBTOTAL THYROIDECTOMY. - Ishrat Rahim1, Mohammad Anwar Memon2, Abdul Rashid Surahio3, Mohammad Qasim Mallah4, Champa Sushel5, Shahnawaz Abro6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVE: This study design to find out andevaluate the frequencyof hypocalcaemia postoperative sub-total thyroidectomyeither temporary or permanent, the proper management of post-operative hypocalcaemia. PLACE AND DURATION OF STUDY: This is a cross sectional study was conducted in the department of surgery Liaquat university hospital Jamshoro. The period of study was three years from January 2016 to December 2018. Liaquat university hospital is tertiary care hospital in the region of Hyderabad and Jamshoro. PATIENTS AND METHOD: Total160 patients were admitted through outpatient department. Male 30 patients (18.75%) female 130 patients (81.25%) with the ratio of male to female (1:4.5) with mean age of male 32.9 years, with mean age of female 34.08 years.160 patients with non-toxic multinodular goiter underwent sub-total thyroidectomy. Other thyroid swellings like toxic goiter, carcinomas excluded from study. RESULTS: Total160 patients were admitted through outpatient department. Male 30 patients (18.75%) female 130 patients (81.25%) with the ratio of male to female (1:4.5) with mean age of male 32.9 years, with mean age of female 34.08 years. 160 patients with non-toxic multinodular goiter underwent sub-total thyroidectomy. From 160 patients who underwent sub-total thyroidectomy eleven patients (06.875%) developed Hypocalcemia. All eleven patients who developed hypocalcemia, all were female, no male patient developed hypocalcemia because goiter is most common in female in our study group number female patients were more as compare to male. Patients developed hypocalcemia during hospital stay post-operatively immediately. They were managed accordingly to give intravenous injection of calcium gluconate. Monitoring of serum calcium level with the follow up of one week, two week and three months on OPD basis, patient were advised serum calcium when they come to OPD. All the patients followed up for 3 months and no one developed Hypocalcemiaduring three months. CONCLUSION: Hypocalcaemiadevelops in elven patients (06.875%),after subtotal thyroidectomy most of the patients on the first the post-operative day. Hypocalcemia can follow subtotal thyroidectomyit can be reduced with preservation of parathyroid glands. In our study no parathyroid gland was identified and tries to preserve blood supply of parathyroid gland, because all patients were operated by senior faculty surgeon associate professor level.